Analytical investigations on helical stair slab - Ahmad, Md. Fozail; Baqi, Abdul; Arif, Mohammed (Journal of Structural Engineering, 2024)
Staircase is an essential part of a building yet it is not given appreciable attention, as far as its actual behavior is concerned, in various leading codes of practice. The helicoidal stair slabs are more difficult because of their complex geometric configurations. The present study is aimed at parametric investigations on helical stair slab using ANSYS software. Deflection and stress contours were obtained. In the first part of the study, the results obtained by earlier researchers were validated. The analytical test result obtained using ANSYS are found to be in close agreement with the results obtained by earlier investigators. In the second part of the study, stair slabs with central angle of 80°, 130° and 180° without landing, with one landing and with two landings were considered. The deflections at the inner, central and outer edges were obtained. Along the width of the stair, the maximum deflection occurs along outer edges and its value decreases as we move towards inner edge whereas along the flight, the deflection reaches its maximum value at mid span. Introduction of landing enhances the maximum deflection. For the stair case with a central angle of 130° and 180°, the stresses σ₁, σ₂, σvon Mises and are found to be significant.